(untitled) (Journal of the Bangladesh Agricultural University, 2026)
The inclusion of Azolla in broiler feed is becoming popular in rural areas to produce meat chicken at a reasonable cost in a sustainable manner. The present study investigated the effects of Azolla inclusion in feeding of broiler chickens under rural farming conditions. For this experiment, conventional and Azolla mixed (10% Azolla with 90% conventional) feedings were carried out with chicks (n=90) and 45 chicks in each feeding group with three replicates and collected data for six weeks. Thirty non-trained panelists carried out the sensory analysis of cooked meat. The data were statistically analyzed. The results showed that mean weight gain, FCR, organs weight except for head as well as sensory parameters of cooked meat were not significantly different while the weight of head was significantly different (p<0.05) between conventional and Azolla mixed feeding groups. The study concluded that the inclusion of 10% dry Azolla in the broiler feed had no negative effects on weight gain, FCR, organs weight and meat sensory characteristics. It is recommended that 10% dry Azolla on weight basis can be included in the feed for the broiler chicken production sustainably in the rural areas without negative effects on the performance of birds and meat sensory quality. J Bangladesh Agril Univ 24(2): 57–63, 2026